Antiquorum Sensing and Antibacterial Activity of Silver Nanoparticles Synthesized by Mutant Klebsiella pneumoniae MTCC 3354 - Arunkumar, Mani; Mahesh, Narayanan; Balakumar, Srinivasan; Sivakumar, Ramalingam; Priyadharshni, S. (Asian Journal of Chemistry, 2013)
Currently there is an urgent need to develop a new strategy for the treatment of antibiotic resistance bacterial pathogen and to reduce the virulent quorum-sensing ability of a microorganism. Microbial synthesis of silver nanoparticles was carried out by using the mutant Klebsiella pneumoniae MTCC 3354 and screened out for antiquorum sensing and antibacterial activity against selected human pathogens. UV-visible spectroscopy and scanning electron microscope study reveals the formation of silver nanoparticles which was predominately spherical shape in the range of 2-20 nm and polydispersed. Silver nanoparticles exhibit enhanced antiquorum sensing and antibacterial activity on selected pathogens. Furthermore, antagonistic activity of amoxicillin, methicillin and ampicillin were increased in the combination of silver nanoparticles against the selected human pathogenic strains. The silver nanoparticles would be alternative strategies for treating the bacterial infection caused by multi-drugs resistance bacteria in upcoming era.